Responsiveness Comparison of the EQ-5D, PROMIS Global Health, And VR-12 Questionnaires In Knee Arthroscopy. Issue 7 (18th July 2016) - Oak, Sameer; Strnad, Greg; Bena, James; Farrow, Lutul D.; Parker, Richard D.; Jones, Morgan H.; Spindler, Kurt P.
Objectives: The EQ-5D, PROMIS 10 Global Health, and VR-12 are generic patient reported outcome (PRO) questionnaires that assess and report patient general health and wellbeing. In choosing a PRO to track patient general health status, it is necessary to consider which measure will be the most responsive to change after treatment. To date, no studies exist comparing the responsiveness among the EQ-5D, PROMIS 10 Global Health, and VR-12. We sought to determine which of the generic PROs were most responsive internally and externally in the setting of knee arthroscopy. Methods: 50 patients undergoing knee arthroscopy were surveyed with a PRO questionnaire pre-operatively and at least 3 months post-operatively. PROs included the EQ-5D, EQ-5D visual analog scale, PROMIS 10 Global Health (PROMIS 10) Physical and Mental components, VR-12 Physical and Mental components, and the Knee injury and Osteoarthritis Outcome Score (KOOS) Pain scale. Internal responsiveness was evaluated by performing paired t-tests on the changes in measures and calculation of two measures of effect size: Cohen's D and standardized response mean (SRM). External responsiveness was evaluated by calculating and comparing Pearson correlation measures between the disease specific reference KOOS Pain and the general PROs EQ-5D, PROMIS 10, and VR-12 changes. General PRO responsiveness measures were compared head to head with the cocor package in R software. Results: Patients were surveyed pre-operatively and a mean of 3.6 months post-operatively with 90% follow-up. For internal responsiveness, the EQ-5D, VR-12 Physical, and PROMIS 10 Physical scales showed a statistically significant improvement in score after treatment and effect size statistics with moderate change (Cohen's D and SRM between 0.5-0.8). Assessing external responsiveness, the EQ-5D, VR-12 Physical, and PROMIS 10 Physical instruments showed the highest correlation with the disease specific reference measure, KOOS Pain (Table 1). For both internal and external responsiveness, the EQ-5D, VR-12 Physical, and PROMIS 10 Physical instruments showed significantly higher responsiveness compared to the other general PRO measures, but no statistical differences among themselves. Conclusion: There is no statistical difference between the EQ-5D, VR-12 Physical, and PROMIS 10 Physical instruments in terms of internal or external responsiveness to change. In tracking longitudinal patient health, researchers and administrators have the flexibility to choose any of the general PROs among the EQ-5D, VR-12 Physical, and PROMIS 10 Physical instruments. We recommend that any study tracking PROs in knee arthroscopy include one of these generic instruments.